The Political Economy of Hydrocarbon Pollution: Assessing Socio-Ecological Sustainability of Nigeria’s Niger Delta Region - Nwozor, Agaptus; Audu, Jacob; Adama, Joseph Ibrahim (International Journal of Energy Economics and Policy, 2018)
The Niger Delta region, which is the hydrocarbon basket of Nigeria, appears to be sitting on an environmental time bomb due to degradation from widespread hydrocarbon pollution. The major sources of environmental degradation in the Niger Delta are oil spillage, gas flaring and improper disposal of wastes from oil drilling operations. Presently, it is estimated that there are over 5,000 massively polluted sites in the Niger Delta. Drawing data from secondary sources, this paper finds that despite the enormity of environmental pollution and its deleterious effects on the socio-economic wellbeing of the Niger Delta region, there is no implementable blueprint or policy for remediation. The paper links the economic cost of environmental pollution to the pervasive poverty and other socio-ecological crises that envelope the region in a smoke of underdevelopment. The paper therefore advocates a clear national remediation policy to sustainably deal with the degraded environment of the region. Keywords: Environmental degradation, hydrocarbon pollution, remediation policy JEL Classifications: O13, P48, Q35, Q52, Q56 DOI: https://doi.org/10.32479/ijeep.7058